Innovation and global intellectual property regulatory regimes: The tension between protection and access in Africa - Nirmalya Syam; Viviana Mu\~noz Tellez (South Centre, 2016)
This paper discusses the participation of African countries in global intellectual property (IP) regimes centred on the World Intellectual Property Organization (WIPO) and the World Trade Organization (WTO), and the implications of the expansion of the scope of IP regimes through bilateral trade and investment agreements. It provides recommendations for an appropriate intellectual property regime to complement Africa's regional integration programmes.
Keywords: 300; Immaterialgüterrechte; Handelsliberalisierung; WTO-Recht; Regionale Wirtschaftsintegration; Afrika